Relación entre el motivo de consulta ortodóncico, el diagnóstico clínico de la maloclusión y el grado de satisfacción postratamiento* parte I: motivo de consulta - Mejía-Villa, Raúl; Flórez-Tobón, Claudia María; Vargas-Zabala, Clara Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2017)
This study was conducted among 250 males and females new patients to identify tne main reasons they had to ask far orthodontics treatment in four dental institutions of Medellin city; likewise, the relation with the clinical malocclusion diagnostic. A survey was used to collect the patients information about their motivation and feelings they had to ask for orthodontics treatment so as the orthodontics clinical diagnostics. The statistical analysis was done using the simple or corrected 7i-square" (X2) test. The results show that: the principal reason of the orthodontics consultation was the esthetics with the 60.1%; the males consultation for esthetics was largest than the females; according as the age increase, the consultation for esthetics decrease, and the consultation for function become more frequent; with the crowded teeth exception, it was found a significative difference between the patients feelings about their orthodontics problems, and the orthodontics clinical diagnostics.